Seminar Series I for Study on Coping Strategies of Non-Chinese students and Families in Chinese Primary Schools in Sarawak - Chai, Elena Gregoria Chin Fern; Wang, Yin Chai; Lee, Jun Choi; Florianna Lendai, Michael Mulok; Awang Ideris, Awang Daud; Siti Mariam, Abdullah; Ngu, Sze Song (2019)
The seminar was held to introduce about the research project to collaborators, sponsors and principals in Chinese Primary Schools in Sarawak. The aims, methods, contributions and final outputs of the project was discussed.